Implementing ECMA Script on Scalable Vector Graphics to Perform Selection Sort Algorithm - Mukhammad Andri Setiawan (Department of Informatics,Faculty of Industrial Technology,Islamic University of Indonesia, 2004)
The Scalable Vector Graphics has emerged a new standard in presenting graphics and animation using the http protocols. By adding some script, we can create animation in a high quality picture. We can then present an SVG document into interactive and dynamic one. It’s possible that technologies such as SVG with its implementation will attract in increasing attention and serious consideration of its possible role as a high quality alternative for many Web presentations that are currently dominated by (X)HTML and CSS.